A critical assessment of pre-election administration on nomination of candidates in 2019 elections in Nigeria / Adekola Abdulazeez Alao and Nurudeen Sikiru Lanre - Alao, Adekola Abdulazeez; Lanre, Nurudeen Sikiru (Universiti Teknologi MARA, 2022)
As important as election to democracy is, election administration for a credible election result is equally germane. Election administration becomes a critical focus of scholars and stakeholders in election. It is unfortunate that Nigeria’s 2019 nomination of candidates in the pre-election administration environment was heralded with tensions, accusations and counter-accusations, irregularities, violence, trade of blames by the ruling and major opposition parties, maladministration among other related issues. It is against this backdrop that this study attempts to examine and analyse nomination of candidates in the pre-election administration of 2019 elections in Nigeria, examine how the stakeholders in election administration have performed in this area. The secondary method of data collection was adopted for the study. The study relies on the theory of political participation and social justice theory. The paper adopts qualitative approach, using descriptive and content analysis to analyse the data obtained. The paper argues that nomination of candidates in the pre-election administration of 2019 election in Nigeria were heralded with a number of irregularities. The paper concludes that some of the shortcomings usually associated with the previous pre-election administration on nomination of candidates in Nigeria are also identified with that of 2019 elections. The identified challenges on the nomination of candidates in the pre-election administration of 2019 elections are discussed and policy options provided.